THE MODEL OF SATISFACTION AND ITS IMPLICATIONS ON EMPLOYEE PERFORMANCE - Zulki Zulkifli Noor (Jurnal Ekonomi, 2023)
The purpose of this study is to understand and analyze: (1) organizational learning; (2) job motivation; (3) job satisfaction, (4) employee performance, and (5) the impact of organizational learning and job motivation on job satisfaction and Effects on employee performance in food and beverage companies in South Jakarta. The research methods used in this study are descriptive survey and explanatory survey. The unit of analysis in this study is the employees of food and beverage companies in South Jakarta, with a sample of 30 people. The nature of the investigation is causal, and the time frame of this study is cross-sectional. According to the research results, it is found that the organizational learning of employees of food and beverage companies in South Jakarta is generally good, the work enthusiasm of employees of food and beverage companies in South Jakarta is generally good, and the employees' satisfaction with food. The beverage companies in South Jakarta are currently rated as good, working Satisfaction affects employee performance. Organizational learning and job motivation affect employee job satisfaction in food and beverage companies in South Jakarta. Organizational learning and job motivation affect employee performance in food and beverage companies in South Jakarta. Employee satisfaction related to employee performance in food and beverage companies in South Jakarta. Work motivation significantly affects job satisfaction, so South Jakarta Food and Beverage companies need to keep this up so that the job satisfaction of employees around South Jakarta Food and Beverage companies remains the same.